FAMILY RHINOPHORIDAE - Nihei, Silvio S. (Zootaxa, 2016)
Only one species of Rhinophoridae has been recorded to Colombia so far, Bezzimyia busckii Townsend, 1919. However, three other species of the genus Bezzimyia are listed in the present catalogue, for they occur on nearby areas and are likely to occur in the country as well.